2021
DOI: 10.1016/j.ejim.2021.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Patient motivation to lose weight: Importance of healthcare professional support, goals and self-efficacy

Abstract: Background: People with obesity (PwO) often struggle to achieve and maintain weight loss. This can perpetuate and/or be influenced by feelings of low motivation. This analysis from ACTION-IO data identified factors associated with PwO motivation to lose weight. Methods: PwO completed an online survey in 11 countries. Exploratory multinomial logistic regression analyses identified independent variables associated with self-report of feeling motivated versus not motivated to lose weight. Results: Data from 10,85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…These results are in line with the study by Dicker et al [18] in which a survey was carried out of people with obesity to identify perceived barriers to weight management, finding that at the time of the interview half of the respondents reported they were not motivated [18]. In the above study, the variables associated with the likelihood of patients being motivated to lose weight fell broadly into three key themes: self-efficacy, setting specific weight loss goals and having a positive and trusting relationship with healthcare professionals [18]. The latter is of the utmost importance, given the social stigma that people with obesity often suffer.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are in line with the study by Dicker et al [18] in which a survey was carried out of people with obesity to identify perceived barriers to weight management, finding that at the time of the interview half of the respondents reported they were not motivated [18]. In the above study, the variables associated with the likelihood of patients being motivated to lose weight fell broadly into three key themes: self-efficacy, setting specific weight loss goals and having a positive and trusting relationship with healthcare professionals [18]. The latter is of the utmost importance, given the social stigma that people with obesity often suffer.…”
Section: Discussionsupporting
confidence: 94%
“…Finally, although the study population has an average age of 65 years, the results obtained are similar to those of other studies [18,21,24,35], so the results obtained could be considered generalizable.…”
Section: Discussionsupporting
confidence: 84%
“…Studies have also demonstrated the important role health professionals play in enhancing their patients’ confidence to manage health conditions, such as chronic diseases and obesity, through education, encouragement and ongoing guidance. 54 , 55 Health professionals may adopt similar approaches to support their patients in developing their confidence for menstrual self-care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on health behaviours have highlighted how confidence in one’s ability to perform a behaviour increases the likelihood they will enact it. 54 , 63 Those who are confident to change their menstrual products at university will therefore do so, reflecting reverse causation.…”
Section: Discussionmentioning
confidence: 99%
“…While patients prefer a holistic approach 50,160,161 , and policymakers demand the HA role 162 , this thesis indicates the internists' predominant role is the medical expert role. This role is embedded in the biomedical model of health and illness-the default model in healthcare 34 .…”
Section: Researchmentioning
confidence: 93%